THE COST-BENEFIT STUDY OF IMPLEMENTING THE KATEPAY PROGRAMME IN SURABAYA - Mardiana Sabela; Amirul Mustofa; Priyanto (Journal Publicuho, 2023)
The purpose of this study is to compare stakeholders from the existing community with the output or advantages and disadvantages of KatePay besides knowing the implementation of the KatePay Program in Surabaya City Schools by how the Government runs the program and what is felt by the community in implementing this program which has been running for one year. Data collection techniques in this study were interviews and Documentation. It then analyzed the data concerning the theory used. The theory applied by the author uses the Cost-Benefit Analysis method, which discusses the identification, benefits, implementation results, and conclusions of the programs being run. Results The first research shows that the KatePay program benefits students more than other stakeholders. Second, KatePay's performance is excellent because it can reduce money transfers and teach students to manage money. This program can also create intelligent and wise students in deciding or doing something. The research implies that it is necessary to socialize intent to all stakeholders so it is not misused.